Effect Of Organizational Citizenship Behavior (Ocb) On Employee Performance Through Job Satisfaction As An Inetervening Variables - Waqiah Waqiah; Muhammad Firdaus; Agustin Hari Prastyowati (LPPM Institut Teknologi dan Sains Mandala, 2021)
Human Resources are the main support in an organization / company. Human resource also plays an important role in improving the performance, productivity and effectiveness of the organization. Good Quality human resources will support the organization in achieving organizational goals. Organizational citizenship behavior is a behavior (extra role) and an important element for the company. This study aims to determine the effect of organizational citizenship behavior on employee performance, the effect of organizational citizenship behavior on job satisfaction and intervening job satisfaction on organizational citizenship behavior on and employee performance. This research is quantitative study, the research subject these are PT Imasco Asiatic employees totaling 5 people. Data collection using questionnaires and data analysis using path analysis. The result of this study are first, organizational citizenship behavior has a significant effect employee performance. Second, organizational citizenship behavior effect the job satisfaction obtained. The last, organizational citizenship behavior don't have a significant effect on employee performance through job satisfaction. Keywords: Organizational Citizenship Behavioron, Employee Performance, Job Satisfaction